Effects of birth body weight and zinc source on growth, gut health, and immune response in weaned piglets - Negrini, Clara; Luise, Diana; Correa, Federico; Virdis, Sara; Serra, Andrea; Bonaldo, Alessio; Manzke, Naiana; Monteiro, Alessandra; Mazzoni, Maurizio; Trevisi, Paolo (Frontiers in Animal Science, 2025)
Zinc (Zn) is an essential trace element for piglets, especially during the challenging post-weaning period. This study investigated the effects of two dietary Zn sources, namely zinc sulfate (ZnSO4) and a porous zinc oxide (pZnO), used at the European-authorized dietary level on piglets of differing birth body weights (BBWs): low (LBBW <1 kg) and normal (NBBW >1 kg). At weaning (25 days, d0), 64 piglets were assigned to four groups based on BBW and Zn source and fed diets that reached a total Zn level of 150 mg/kg. Body weight was monitored weekly until d21. On d9 and d21, 32 piglets were slaughtered for gut histology, immunohistochemistry, gene expression, blood markers, pH measurement, microbiota, and short-chain fatty acid (SCFA) analysis. The NBBW group had higher BW throughout the study (P<0.01), confirming BBW as a key factor influencing growth and physiological maturity. The pZnO group tended to have a higher average daily gain in the periods d0-d9 and d9-d14 (P<0.10). The pZnO reduced jejunum pH at d21 (P = 0.02). The interaction between diet and BBW influenced the nuclear factor kappa B subunit 2 (NFKB2) expression at d9 (P = 0.03), with LBBW piglets fed ZnSO4 showing higher expression. At d21, the interaction between diet and BBW affected the villus height (P = 0.05) and the absorptive mucosal surface (P = 0.02), which were higher in the NBBW group than in the LBBW group fed ZnSO4, while no difference was observed between the NBBW and LBBW groups fed the pZnO. Differences in microbiota beta diversity were associated with BBW (P = 0.07 at d9; P = 0.03 at d21), and taxa abundance varied with Zn source and BBW. Overall, the results demonstrate that the pZnO positively influenced gut health and performance in weaned piglets, particularly in the LBBW group. The differential response to Zn sources according to BBW suggests that tailored mineral strategies could help mitigate the effects of weaning stress in vulnerable piglets.